An aptamer folding‐based sensory platform decorated with nanoparticles for simple cocaine testing. Issue 4 (23rd June 2016) - Guler, Emine; Bozokalfa, Guliz; Demir, Bilal; Gumus, Zinar Pinar; Guler, Bahar; Aldemir, Ebru; Timur, Suna; Coskunol, Hakan
Abstract : The consumption of illicit drugs such as cannabis, cocaine, and amphetamines is still a major health and social problem, creating an abuse in adults especially. Novel techniques which estimate the drug of abuse are needed for the detection of newly revealed psychoactive drugs. Herein, we have constructed a combinatorial platform by using quantum dots (QDs) and gold nanoparticles (AuNPs) as well as a functional aptamer which selectively recognizes cocaine and its metabolite benzoylecgonine (BE). We have called it an aptamer folding‐based sensory device (AFSD). For the fabrication of AFSD, QDs were initially immobilized onto the poly‐L‐lysine coated μ‐well surfaces. Then, the AuNP‐aptamer conjugates were bound to the QDs. The addition of cocaine or BE caused a change in the aptamer structure which induced the close interaction of AuNPs with the QDs. Hence, quenching of the fluorescence of QDs was observed depending on the analyte amount. The linearity of cocaine and BE was 1.0–10 nM and 1.0–25 μM, respectively. Moreover, the limits of detection for cocaine and BE were calculated as 0.138 nM and 1.66 μM. The selectivity was tested by using different interfering substances (methamphetamine, bovine serum albumin, codeine, and 3‐acetamidophenol). To investigate the use of AFSD in artificial urine matrix, cocaine/BE spiked samples were applied. Also, confirmatory analyses by using high performance liquid chromatography were performed. It is shown that AFSD has a good potential for testing the cocaine abuse and can be easily adapted for detection of various addictive drugs by changing the aptamer according to desired analytes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this work, we aimed to develop a new, simple and confident sensory platform for cocaine detection. For the fabrication of this test system, surface of μ‐well plates was modified with quantum dots (QDs) and then cocaine‐binding aptamer modified gold nanoparticles (Apt‐AuNP) were covalently attached to the QDs. Detectable signals were obtained owing to the target‐induced conformational change of aptamer which gives rise to close interaction of QDs with their quencher, AuNPs. Hence, decrease in fluorescence intensity as a cocaine response was recorded. The developed test system – called as Aptamer Folding based Sensory Device, (AFSD) ‐ was evaluated in terms of main analytical performance parameters for both cocaine and its metabolite BE. Afterwards, AFSD was successfully applied to the synthetic biological fluids for both cocaine and BE analysis.